2019
DOI: 10.3389/fevo.2019.00285
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Spatiotemporal Variation and Carry-Over Effects in a Migratory Alpine Songbird

Abstract: For migratory animals, events at one stage of the annual cycle can produce constraints or benefits that carry over to subsequent stages. Differing life-history strategies among individuals can influence the expression of these carry-over effects, leading to pronounced within-population variation in migration. For example, reproductive roles can drive spatiotemporal segregation during the non-breeding season and promote sex-specific carry-over effects, such as reproductive effort affecting autumn migration beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 91 publications
2
49
0
Order By: Relevance
“…It has been suggested that these longer stopovers after the Sahara crossing are used to assess the environmental conditions in Europe and could therefore be used to buffer interannual variation in the timing of spring. Similar patterns were found in migratory Horned larks (Eremophila alpestris) that performed long stopovers before reaching their high elevation breeding grounds 20 . In addition to a general adjustment in the arrival time, wheatears can adjust the arrival-breeding interval according to their arrival dates and spring progression 34 , strongly suggesting that, to some extent, wheatears are able to match their migration and breeding activities with local conditions and seasonally limited resources 37 .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It has been suggested that these longer stopovers after the Sahara crossing are used to assess the environmental conditions in Europe and could therefore be used to buffer interannual variation in the timing of spring. Similar patterns were found in migratory Horned larks (Eremophila alpestris) that performed long stopovers before reaching their high elevation breeding grounds 20 . In addition to a general adjustment in the arrival time, wheatears can adjust the arrival-breeding interval according to their arrival dates and spring progression 34 , strongly suggesting that, to some extent, wheatears are able to match their migration and breeding activities with local conditions and seasonally limited resources 37 .…”
Section: Discussionsupporting
confidence: 61%
“…3.500 km). However, the high-elevation breeding sites are, to some extent, comparable with those of the more northerly breeding populations; alpine breeding grounds are characterised by strong seasonal climate and food resources, and the duration of snow cover and the short season limits the reproductive period and requires accurate timing of life-history events 19,20 . The similarity is also re ected in life-history traits, such as a single clutch per year, of the wheatear subpopulations (leucorhoa) and the southern Alpine populations 13,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ring ouzels migrate much faster in the spring than in the autumn, a pattern commonly observed in migratory species in Europe 38 . However, this contrasts with the migration strategy of other mountain or arctic bird species, that make prolonged pre-breeding stopovers at lower elevations or latitudes not far from their reproductive grounds, waiting there for the snowmelt at their nearby breeding sites and/or building fat reserves 39,40 . With their daily transhumance, ring ouzels have thus found an innovative solution to cope with the highly seasonal and unpredictable breeding environment that prevails at high elevation.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, ring ouzels migrate much faster in the spring than in the autumn, a pattern commonly observed across various migration yways and species (Nilsson et al 2013;Schmaljohann 2018). However, this contrasts with the migration strategy of other mountain or arctic bird species, that make prolonged pre-breeding stopovers at lower elevations or latitudes not far from their reproductive grounds, waiting there for the snowmelt at their nearby breeding sites and/or building fat reserves (de Zwaan et al 2019;Kölzsch et al 2016). With their daily elevational movements, ring ouzels have thus found an innovative solution to cope with the highly seasonal and unpredictable breeding environment that prevails at high elevation.…”
Section: Discussionmentioning
confidence: 99%